User engagement against online hate speech in Japan: Driven by high perceptions of personal abilities and benefits - Löschke, Ayaka (Conference “Diverse Approaches to Hate Speech: debates, Challenges, and Controversies”, 2022)
User engagement against online hate speech has supplemented professional content moderation and constitutes an increasingly indispensable part of content moderation. Considering three determinants of user engagement against online hate speech that were identified in a German case study, this research conducts a Japanese case study. Japanese users launched the #Internet Rightists Ban Festival in 2018 and are continuing their engagement. As a result, about 963,000 videos and 3,900 channels have been removed from YouTube About 250 million tweets and 11,000 accounts have been deleted from Twitter. The YouTube channels and Twitter accounts of prominent right-wing publicists have also been permanently or temporarily banned. What drove the participants to carry out and maintain their engagement? What type of users attended the festival and took the leadership? This research asks these questions, conducting an inductive qualitative analysis of 3,821 tweets and classifying 1,038 participants. The sample was selected from tweets that were posted during three different periods between 2018 and 2020. It is argued that the Japanese user engagement has been driven especially by the perception of personal abilities, such as gaming and comment-writing skills, and the perception of personal benefits, especially from gamification and irony. This research also identifies participants’ left-wing political orientation as an important factor in keeping a sense of responsibility and taking leadershi
Keywords: online activism; Japan; incivility online; hate speech; irony; gamification